The aging clock : the pineal gland and other pacemakers in the progression of aging and carcinogenesis : Third Stromboli Conference on Aging and Cancer - Pierpaoli, Walter; Regelson, William; Fabris, Nicola ((Annals of the New York Academy of Sciences,, 1994)
Part I. An introduction to the pineal gland: ontogeny, physiology, and evolutionary aspects. - Part II. Mechanism and pathology of CNS pacemakers and signalling systems. - Part III. Theories, models, and emerging hypotheses and facts on the mechanism of senescence. - Part IV. Aging of the brain, dementia, Alzheimer´s disease: theories and new facts. - Part V. Chronoimmunology, pineal-circadian control of natural and acquired immunity. - Part VI. Neuroendocrine and immune aging : role of the pineal and other pacemakers. - Part VII. Pharmacological, prophylactical, and therapeutical interventions on the pineal aging clock: rationale and results. - Part VIII. Pineal, melatonin, and DHEA mechanism in aging and oncogenesis.